The main factors affecting key characteristics of fuel-efficient driving and safe driving - Tan, Yong Ren (Universiti Sains Malaysia, 2019)
In this research, qualitative and quantitative research methods are used to determine the correlation between key characteristics of fuel-efficient driving and safe driving. It aims to give correct motivation on fuel-efficient driving towards safe driving. The key characteristics of fuel-efficient and safe driving are identified and ranked. The relationships for both variables are then been analysed. To ease the calculation process, scaling method is used to quantify each of key driving characteristics. The ranking and scaling are done for fuel-efficiency according to the degree of fuel improvement based on the level of idling, accelerating and braking, as well as speed of travel. While for safe driving, tendency for accident to occur and degree of fatality caused by respective driving characteristics. The scale will be different by approach used so that the comparison can be made on the level of variation and accuracy. Several approaches were used to obtain numerical values for correlation coefficient between fuelefficient driving and safe driving. The average correlation coefficient between key characteristics of fuel-efficient driving and safe driving obtained is r = 0.423 which has medium positive impact in overall, with p-value of 0.097 which is less significant.